Black Sonic Traditions as a Resource for Teaching and Learning Ethics - Cook, Julian Armand (Journal of the Society of Christian Ethics, 2025)
The sonic and aesthetic nuances of Black religious traditions have often gone underexamined as critical resources for Christian ethical reflections and scholarship. Many Christian ethics scholars have focused on text-based analyses of lyrics, doctrinal statements, sermons, and archives. More teaching and scholarship on how the sounds and aesthetics performed in specific Black religious contexts could enrich Christian ethics discourses. But how should teachers responsibly engage the Black religious sonic in teaching and learning Christian ethics? This essay posits Black religious sounds and aesthetics as a site for contesting, deconstructing, and constructing ontologies, notions of communal flourishing, and racial, gender, and sexual identities. The result is the assemblage of new knowledge critically resourced by sound, music, and aesthetics that emphasizes how sound facilitates communal moral formation. Specifically, I look to the 2018 Aretha Franklin Homegoing as a site for Black religious sonic sources and ethical dilemmas.